PERAN DPRD KOTA SURABAYA DALAM PENGAWASAN DAN MONITORING KEUANGAN PUBLIK PADA PENGOLAAN APBD - Firza Alifatuz Zhulfa; Nasywa Putri Kumara; Eva Hany Fanida; Ravienda Anita Fitrie (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Regional Revenue and Expenditure Budget (APBD) plays a strategic role in the implementation of local government and therefore requires effective and accountable oversight. In this context, the Regional House of Representatives (DPRD) of Surabaya City exercises legislative, budgeting, and supervisory functions as stipulated in Law Number 23 of 2014 on Regional Government. This study aims to analyze the role of the Surabaya City DPRD in overseeing and monitoring APBD management, covering the planning stage through discussions of the General Budget Policy and Provisional Budget Priorities and Ceilings (KUA–PPAS), budget implementation, and follow-up actions on audit results issued by the Audit Board of Indonesia (BPK). The research employs a qualitative descriptive approach, with data collected through document analysis and a review of relevant literature. The research results show that DPRD oversight is quite effective in maintaining fiscal stability and administrative compliance, as reflected in the budget deficit remaining below 2% and the follow-up to audit recommendations reaching 98.38%. However, the decline in capital expenditure absorption from 92.78% (2023) to 72.53% (2024) indicates that oversight at the implementation stage is not yet fully optimal. Therefore, DPRD oversight is considered strong administratively, but not yet optimal in improving the quality of development spending Keywords: DPRD; APBD; Supervisions; Regional Finances; Effectiveness